A CASE OF LASSA FEVER IN PAKISTANI SOLDIER ON UNITED NATION MISSION IN LIBERIA: Lassa Fever – A Case Report - Tariq, Lt Col Muhammad; Mehmood, Asad; ., Saleemullah (Pakistan Armed Forces Medical Journal, 2010)
Lassa fever is an acute viral haemorrhagic fever endemic in West Africa. It has been reported from Sierra Leone, Guinea, Liberia, and Nigeria1.. Lassa fever is also the most common hemorrhagic fever that is exported beyond its endemic area to Europe and other parts of the world2. One Such case of a Pakistani soldier on united nations mission in Liberia is reported